The impact of crime on apartment prices: evidence of Stockholm, Sweden - Vania Ceccato; Mats Wilhemson (European Regional Science Association (ERSA), 2010)
This study uses data over 9600 apartment sales in Stockholm, Sweden, to assess the impact of crime on property prices. Using two-stage analysis, the study first employs hedonic pricing modelling to estimate the impact of crime controlling for other factors (property and neighbourhood characteristics). Then, the willingness to pay is calculated for a certain property having as a function crime together with other house and area attributes. GIS is used to combine apartment sales by co-ordinates with offences, land use characteristics and demographic and socio-economic data of the population. The novelty of this research is threefold. First, it explores a set of land use attributes created by spatial techniques in GIS in combination with detailed geographical data in hedonic pricing modelling. Second, the effect of crime in neighboring zones at one place can be measured by incorporating spatial lagged variables of offence rates into the model. Third, the study provides evidence of the impact of crime on housing prices from a capital city from a welfare state country, something otherwise lacking in the international literature. Our results indicate that total crime rates showed no effect on apartment prices but when the offences were break down by types, violence, residential burglary, vandalism and robbery had individually a significant effect on property values.
Keywords: 330; offences; residential property value; hedonic modelling; GIS; spatial modelling